KONSTRUKSI LINGKUNGAN BELAJAR DAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA PADA MATA KULIAH BIOLOGI UMUM - Kurratul Aini; Fahmy Armanda (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2021)
The aim this study was to determine the relationship between the learning environment and critical thinking skills of Biology Education students in general biology courses. The sample of research was 110 Biology Education students who contracted General Biology courses. The instrument used question of critical thinking skill by Ennis and the constructivist learning environment survey (CLES) by Fisher. Data analysis using Pearson correlation. The results obtained the highest average score on the Basic support indicator of 5.34 and the lowest average on the Strategy and tactics indicator with of 2.99. On constructivist learning environment survey the highest average score on the Student negotiation factor was 23.80 and the lowest score was on the Shared control factor of 16.50. Pearson correlation test results showed a significance value of 0.143> 0.05 that mean there was no correlation between variables. There is no relationship between the learning environment and critical thinking skills of Biology Education students in general biology courses. The reason for the lack of critical thinking skills and the construction of the learning environment is that students are not right in using their cognitive strategies.